Penerapan Teknologi Enterprise Resource Planning Menggunakan Modul Inventory Management dengan Metode FIFO Berbasis Website Pada CV Pandan Mas Sampit - Hapsari, Nur Septia Dwi; Mustaqiem, Mustaqiem; Minarni, Minarni (TIN: Terapan Informatika Nusantara, 2021)
In the era of information technology today, it has an important role, one of which for companies is that the activities carried out will be faster, more accurate and effective in order to minimize unexpected errors. PT. Wheat is a company engaged in the cigarette industry that was established in 1979 and is a subsidiary of PT. Gudang Garam. PT. Wheat has several subsidiaries, one of which is CV. Pandan Mas to become a distributor in Sampit. In the business process, CV. Pandan Mas has several problems, namely experiencing a difference in the stock of goods in the warehouse when goods enter or leave, the warehouse storage management that is applied still uses a semi-manual and handwritten data collection system during stock recapitulation, and in making other processes. Of course, this still allows for human error, whether intentional or not, and allows for a decrease in product quality. The FIFO method itself is a method that applies a first in first out system, namely the first goods to arrive are the first goods out in order to make the stock of goods more regular and there is no accumulation of goods and a decrease in product quality. From the problems above, it can be seen that there is a need for an application of enterprise resource planning technology using the Inventory Management module with the FIFO method which is expected to facilitate business processes so that they can run smoothly and problems that arise can be minimized